Faithful Place - French, Tana. (New York : Viking, 2010)
Detective Frank Mackey finds a suitcase belonging to his first love, Rosie Daly, behind a fireplace in a derelict house on Faithful Place. The third novel of the Dublin murder squad.
Keywords: Missing persons -- Fiction; First loves -- Fiction; Police -- Ireland -- Dublin -- Fiction; Dublin (Ireland) -- Fiction